Pathogenic potential of Metarhizium anisopliae and Lecanicillium longisporum on tea mosquito bug, Helopeltis theivora Waterhouse (Hemiptera: Miridae) - Nagaraj Santhana Bharathi; Pannerselvam Mahendran; Krishnaswamy Sujatha; Shanmugam Ashokraj; Thattante Parambil Rabeesh (Journal of Basic and Applied Zoology, 2022)
Abstract Background The study was focused on identifying the pathogenic potential of native entomopathogenic fungi (EPF) viz., Metarhizium anisopliae (Metsch.) and Lecanicillium longisporum (Zimm.) against adult tea mosquito bug (TMB), Helopeltis theivora (Waterhouse) under in vitro conditions. Results Four EPF were isolated and the sequence has deposited to NCBI Genbank with accession numbers of MZ930378 (Metarhizium anisopliae isolate UPASI_1), MZ930384 (Lecanicillium longisporum isolate UPASI_2), MZ930388 (Metarhizium anisopliae isolate UPASI_3) and MZ930389 (Metarhizium anisopliae isolate UPASI_4). Isolates were evaluated against adult TMB using dipping and direct spray methods under in vitro conditions. The M. anisopliae isolates achieved 100 and 69–81% of adult mortality in dipping and direct spray method, respectively after the 10th day of application with 1 × 109 spores/ml. Among the tested isolates, a significant (p < 0.001) and highest mortality were observed in M. anisopliae (MZ930388). On the other hand, spraying of L. longisporum with 1 × 109, 1 × 107 and 1 × 105 spores/ml caused the adult mortality of 76, 55 and 46% respectively after the 10th day of application. Conclusions The study found that the indigenous EPF, M. anisopliae (MZ930388) was an effective and promising biocontrol agent against adult TMB under in vitro conditions.